Stress Analysis of Crank Using Pro/E and Ansys - Jose Ananth Vino, V.; Kumar, Nilesh; Pratap Singh, Rahul; Purkayastha, Rajesh; Kumar, Ravindra; Ahmed, Razi (International Journal of Psychosocial Rehabilitation, 2019)
The project deals with the analysis of stresses induced in cranks using PRO/E and ANSYS software. Initially, theoretical analysis has been done to find out the stresses induced in the crank. Then the crank is modeled using PRO/E and is imported to ANSYS software. The model is then analyzed for different stresses and compared with the theoretical value obtained.